The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12886-020-01757-7
|View full text |Cite
|
Sign up to set email alerts
|

Sub-optimal gain in vision in retinal vein occlusion due to under-treatment in the real world: results from an open-label prospective study of Intravitreal Ranibizumab

Abstract: Background Macular edema secondary to retinal vein occlusion (RVO) is an important cause of loss of vision. Intravitreal injections (IVI) of anti-vascular endothelial growth factor (VEGF) are the standard of care in this disease, as shown in numerous randomized controlled trials. The purpose of this study was to study the efficacy and safety of ranibizumab, an anti-VEGF agent, in the real-world setting. Methods This was 48 weeks, open-label, prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Additionally, patients' lower educational status also means that they fail to perceive the benefits of treatment and are often unsatisfied with visual outcomes [6]. These factors mean that the majority of physicians in the developing world, including India, are forced to adopt a PRN treatment protocol from baseline, as evidenced by a lot of studies published from the region [10,12,16]. Previous studies from the west have also shown that about a third of the patients can do well even without the loading dose, provided a close follow-up can be maintained and reinjections given at the first instance of requirement based on established retreatment criteria [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients' lower educational status also means that they fail to perceive the benefits of treatment and are often unsatisfied with visual outcomes [6]. These factors mean that the majority of physicians in the developing world, including India, are forced to adopt a PRN treatment protocol from baseline, as evidenced by a lot of studies published from the region [10,12,16]. Previous studies from the west have also shown that about a third of the patients can do well even without the loading dose, provided a close follow-up can be maintained and reinjections given at the first instance of requirement based on established retreatment criteria [17].…”
Section: Discussionmentioning
confidence: 99%
“…While a fixed or a treat-and-extend regimen can result in better anatomical and morphological improvement than a PRN regimen for the treatment of nAMD, 32 in resource-poor settings a PRN regimen with strict follow-up can provide comparable results with much reduced expenses. 20 , 33 A further reduction in the expenses can be brought about with the use of biosimilar ranibizumab. 20 In real-life situations the burden of repeated injections may make it difficult to sustain treatments with biologics for long periods of time, more so with the higher cost of the innovator drug.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-optimal visual gain may be due to undertreatment in real-world setting. [ 26 ] Presently, there is insufficient evidence on efficacy and cost-effectiveness of anti-VEGF in ischemic CRVO. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%